Accessibility and scalability in collaborative e-commerce environments. (1st December 2008) - Khoury, Michel; Shen, Xiaojun; Shirmohammadi, Shervin
Much advancement has recently occurred in e-commerce systems' interfaces. Product specifications listings combined with pictures are no longer considered the benchmark for e-commerce interfaces. Albeit commercial websites have not ventured in these developments, academic research has tried, through this progression, to mimic the real-life shopping experience. Shopping in real-life is a social experience with other components attached to it: customers consult with experts and shop in groups benefiting from others' opinions. These aspects, when lacking, can lead to reduction in sales. In this article, we build on a collaborative e-commerce system. The system adopts concepts from virtual environments, allowing customers to interact with 3D models of the items of interest in the virtual shop as well as share those items with other customers or ask for expert opinions, in real-time. Our system addresses accessibility, by using Macromedia Shockwave, a widely deployed player, and therefore avoids the need of unusual plug-ins, such as Virtual Reality Modelling Language viewers. In addition, the system addresses scalability, by using a peer-to-peer communications architecture to support a number of geographically dispersed customers on the internet simultaneously.